The COP9 signalosome inhibits Cullin-RING E3 ubiquitin ligases independently of its deneddylase activity. Issue 2 (3rd April 2018) - Suisse, Annabelle; Békés, Miklós; Huang, Tony T.; Treisman, Jessica E.
ABSTRACT: The COP9 signalosome inhibits the activity of Cullin-RING E3 ubiquitin ligases by removing Nedd8 modifications from their Cullin subunits. Neddylation renders these complexes catalytically active, but deneddylation is also necessary for them to exchange adaptor subunits and avoid auto-ubiquitination. Although deneddylation is thought to be the primary function of the COP9 signalosome, additional activities have been ascribed to some of its subunits. We recently showed that COP9 subunits protect the transcriptional repressor and tumor suppressor Capicua from two distinct modes of degradation. Deneddylation by the COP9 signalosome inactivates a Cullin 1 complex that ubiquitinates Capicua following its phosphorylation by MAP kinase in response to Epidermal Growth Factor Receptor signaling. The CSN1b subunit also stabilizes unphosphorylated Capicua to control its basal level, independently of the deneddylase function of the complex. Here we further examine the importance of deneddylation for COP9 functions in vivo . We use an uncleavable form of Nedd8 to show that preventing deneddylation does not reproduce the effects of loss of COP9. In contrast, in the presence of COP9, conjugation to uncleavable Nedd8 renders Cullins unable to promote the degradation of their substrates. Our results suggest that irreversible neddylation prolongs COP9 binding to and inhibition of Cullin-based ubiquitin ligases.